2020
DOI: 10.1101/2020.05.30.125757
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Patterns of speciation are similar across mountainous and lowland regions for a Neotropical plant radiation (Costaceae:Costus)

Abstract: Author Contributions: Study was designed by OMV, DLG and KMK. KMK curated the plant collection used for genomic sampling. OMV, DLG and KMK collected the data. Phylogenetic analyses were conducted by OMV. Species richness and topographic complexity analyses were conducted by BG; all other geographic and climatic analyses were conducted by DLG. Juarez (UCSC) for help with field collecting, and Edgardo Ortiz for assistance with the analysis of the transcriptomic data. All field research was conducted with appropr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 90 publications
1
10
0
Order By: Relevance
“…Mellitophilous flowers are most often subtended by green, often leafy, bracts while ornithophilous flowers are subtended by bright red, orange, or yellow bracts. Previous phylogenetic studies have estimated multiple shifts in pollination syndromes during the evolution of Neotropical Costus, including shifts to mellitophilous pollination syndromes and subsequent regains of ornithophilous flowers (Specht, 2006;Salzman et al, 2015;Valderrama et al, 2020;Vargas et al, 2020), mainly through sympatric speciation events (André et al, 2016). These results suggest that shifts in traits leading to distinct pollination syndromes, together with reproductive isolation via reinforcement, may account for the rapid radiation observed in this Neotropical clade.…”
Section: Introductionmentioning
confidence: 75%
“…Mellitophilous flowers are most often subtended by green, often leafy, bracts while ornithophilous flowers are subtended by bright red, orange, or yellow bracts. Previous phylogenetic studies have estimated multiple shifts in pollination syndromes during the evolution of Neotropical Costus, including shifts to mellitophilous pollination syndromes and subsequent regains of ornithophilous flowers (Specht, 2006;Salzman et al, 2015;Valderrama et al, 2020;Vargas et al, 2020), mainly through sympatric speciation events (André et al, 2016). These results suggest that shifts in traits leading to distinct pollination syndromes, together with reproductive isolation via reinforcement, may account for the rapid radiation observed in this Neotropical clade.…”
Section: Introductionmentioning
confidence: 75%
“…We also test for alignment in the direction of QTL effects with each other and with the parental trait differences that would indicate adaptive pleiotropy and/or linkage that could promote the evolution and maintenance of floral mechanical isolation in this system. Multilocus phylogenetic data show that they are very recently diverged species, and part of a larger recent and rapid Neotropical species radiation (Vargas et al, 2020). The species are sympatric throughout much of Central and Northwestern South America, but the range of C. pulverulentus extends further north into Mexico and Cuba.…”
Section: Introductionmentioning
confidence: 98%
“…Here, we examine the genetic architecture underlying floral divergence between two species of spiral gingers (genus Costus) living in sympatry and sharing their primary hummingbird pollinator but placing pollen on either the bird's bill or forehead. Previous studies in this system have established pollinator identity and visitation rates, the close phylogenetic relatedness of the species, the high relative importance of floral trait divergence to overall reproductive isolation, and the extent of hybridization and introgression in sympatry (Kay, 2006;Kay & Schemske, 2003, 2008Surget-Groba & Kay, 2013;Vargas et al, 2020). Unlike most long-lived perennial tropical plants, Costus can be grown to flowering in large numbers in the glasshouse in order to use a QTL mapping approach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Speciation may increase with altitude (Weir 2006;Drummond et al 2012;Pouchon et al 2018;Quintero & Jetz 2018;Vasconcelos et al 2020), or under environmental perturbations, such as Andean orogenic activity (Weir 2006;Madriñán et al 2013;Lagomarsino et al 2016;Pouchon et al 2018;Quintero & Jetz 2018;Esquerré et al 2019;Vasconcelos et al 2020), or seasonal climatic variations (Simon et al 2009;Fouquet et al 2014;Pinto-Ledezma et al 2017;Igea & Tanentzap 2020). However, this view is not without controversy, as some studies found that past environmental changes did not affect diversification, and that there are similar diversification patterns among Neotropical regions (Smith et al 2014;Harvey et al 2020;Vargas et al 2020). Unfortunately, up to date, most studies investigating this question focus on long-term dynamics of particular clades or in continental Neotropical scale patterns at shallow evolutionary times, i.e.…”
Section: Introductionmentioning
confidence: 99%